Reduction in nonabstinent WHO drinking risk levels and change in risk for liver disease and positive AUDIT-C scores: prospective 3-year follow-up results in the U.S. general population - Knox, Justin; Mann, Karl (Alcoholism, 2018)
Abstinence is often the treatment aim for alcohol use disorders (AUD), but this may deter individuals who prefer drinking reduction goals from entering treatment, and be an overly restrictive end point in alcohol clinical trials. Nonabstinent drinking reductions that predict improvement in how individuals feel or function may be useful clinical trial outcomes, for example, reductions in the 4-category World Health Organization (WHO) drinking risk levels. To investigate the clinical relevance of these reductions, we examined their relationship with 2 outcomes of interest to medical providers: liver disease, and positive scores on an alcohol screening measure.